Structural and magnetic properties of ternary Fe1–xMnxPt nanoalloys from first principles - Gruner, Markus E.; Entel, Peter (Beilstein Journal of Nanotechnology, 2011)
Background: Structural and magnetic properties of binary Mn–Pt and ternary Fe1–xMnxPt nanoparticles in the size range of up to 2.5 nm (561 atoms) have been explored systematically by means of large scale first principles calculations in the framework of density functional theory. For each composition several magnetic and structural configurations have been compared.Results: The concentration dependence of magnetization and structural properties of the ternary systems are in good agreement with previous bulk and thin film measurements. At an intermediate Mn-content around x = 0.25 a crossover between several phases with magnetic and structural properties is encountered, which may be interesting for exploitation in functional devices.Conclusion: Addition of Mn effectively increases the stability of single crystalline L10 particles over multiply twinned morphologies. This, however, compromises the stability of the ferromagnetic phase due to an increased number of antiferromagnetic interactions. The consequence is that only small additions of Mn can be tolerated for data recording applications.
Keywords: density functional theory; Fe–Pt; magnetic data recording; magnetostructural transition; Mn–Pt

(untitled) - Toshima, N.; Yonezawa, T. (New J. Chem., 1998)

(untitled) - Šafařík, I.; Šafaříková, M. (Monatsh. Chem., 2002)

(untitled) - Pankhurst, Q. A.; Conolly, J.; Jones, S. K.; Dobson, J. (J. Phys. D: Appl. Phys., 2003)

(untitled) - Tartaj, P.; del Puerto Morales, M.; Veintemillas-Verdaguer, S.; Gonzáles-Carreño, T.; Serna, C. J. (J. Phys. D: Appl. Phys., 2003)

(untitled) - Ferrando, R.; Fortunelli, A.; Johnston, R. L. (Phys. Chem. Chem. Phys., 2008)

(untitled) - Zayak, A. T.; Beckman, S. P.; Tiago, M. L.; Entel, P.; Chelikowsky, J. R. (J. Appl. Phys., 2008)

(untitled) - Alloyeau, D.; Ricolleau, C.; Mottet, C.; Oikawa, T.; Langlois, C.; Bouar, Y. L.; Braidy, N.; Loiseau, A. (Nat. Mater., 2009)

(untitled) - Kita, E.; Oda, T.; Kayano, T.; Sato, S.; Minagawa, M.; Yanagihara, H.; Kishimoto, M.; Mitsumata, C.; Hashimoto, S.; Yamada, K.; Ohkohchi, N. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Shao, H.; Yoon, T.-Y.; Liong, M.; Weissleder, R.; Lee, H. (Beilstein J. Nanotechnol., 2010)

(untitled) - Sun, S.; Murray, C. B.; Weller, D.; Folks, L.; Moser, A. (Science, 2000)

(untitled) - Kodama, H.; Momose, S.; Ihara, N.; Uzumaki, T.; Tanaka, A. (Appl. Phys. Lett., 2003)

(untitled) - Sun, S. (Adv. Mater., 2006)

(untitled) - Weller, D.; Moser, A. (IEEE Trans. Magn., 1999)

The Physics of Ultra-High-Density Magnetic Recording - Plumer, M. L.; van Ek, J.; Weller, D. (Springer, 2001)

(untitled) - Yang, X.; Liu, C.; Ahner, J.; Yu, J.; Klemmer, T.; Johns, E.; Weller, D. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2004)

(untitled) - Held, G. A.; Zeng, H.; Sun, S. (J. Appl. Phys., 2004)

(untitled) - Perez, A.; Dupuis, V.; Tuaillon-Combes, J.; Bardotti, L.; Prével, B.; Bernstein, E.; Mélinon, P.; Favre, L.; Hannour, A.; Jamet, M. (Adv. Eng. Mater., 2005)

(untitled) - Tournus, F.; Tamion, A.; Blanc, N.; Hannour, A.; Bardotti, L.; Prével, B.; Ohresser, P.; Bonet, E.; Epicier, T.; Dupuis, V. (Phys. Rev. B, 2008)

(untitled) - Solovyev, I. V.; Dederichs, P. H.; Mertig, I. (Phys. Rev. B, 1995)

(untitled) - Stahl, B.; Ellrich, J.; Theissmann, R.; Ghafari, M.; Bhattacharya, S.; Hahn, H.; Gajbhiye, N. S.; Kramer, D.; Viswanath, R. N.; Weissmüller, J.; Gleiter, H. (Phys. Rev. B, 2003)

(untitled) - Miyazaki, T.; Kitakami, O.; Okamoto, S.; Shimada, Y.; Akase, Z.; Murakami, Y.; Shindo, D.; Takahashi, Y. K.; Hono, K. (Phys. Rev. B, 2005)

(untitled) - Dmitrieva, O.; Rellinghaus, B.; Kästner, J.; Liedke, M. O.; Fassbender, J. (J. Appl. Phys., 2005)

(untitled) - Wiedwald, U.; Han, L.; Biskupek, J.; Kaiser, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Yang, B.; Asta, M.; Mryasov, O. N.; Klemmer, T. J.; Chantrell, R. W. (Scr. Mater., 2005)

(untitled) - Müller, M.; Albe, K. (Acta Mater., 2007)

(untitled) - Gruner, M. E.; Rollmann, G.; Entel, P.; Farle, M. (Phys. Rev. Lett., 2008)

(untitled) - Gruner, M. E.; Entel, P. (J. Phys.: Condens. Matter, 2009)

(untitled) - Dai, Z. R.; Sun, S.; Wang, Z. L. (Surf. Sci., 2002)

(untitled) - Wang, R.; Dmitrieva, O.; Farle, M.; Dumpich, G.; Ye, H. Q.; Poppa, H.; Kilaas, R.; Kisielowski, C. (Phys. Rev. Lett., 2008)

(untitled) - Baletto, F.; Ferrando, R. (Rev. Mod. Phys., 2005)

(untitled) - van de Waal, B. W. (J. Chem. Phys., 1989)

(untitled) - Raoult, B.; Farges, J.; de Feraudy, M.-F.; Torchet, G. (Philos. Mag. B, 1989)

(untitled) - Doye, J. P. K.; Calvo, F. (Phys. Rev. Lett., 2001)

(untitled) - Cleveland, C. L.; Landmann, U. (J. Chem. Phys., 1991)

(untitled) - Hohenberg, P.; Kohn, W. (Phys. Rev., 1964)

(untitled) - Ung, D.; Tung, L. D.; Caruntu, G.; Delaportas, D.; Alexandrou, I.; Prior, I. A.; Thanh, N. T. K. (CrystEngComm, 2009)

(untitled) - Paz-Borbon, L.; Johnston, R.; Barcaro, G.; Fortunelli, A. (Eur. Phys. J. D, 2009)

(untitled) - Wiedwald, U.; Klimmer, A.; Kern, B.; Han, L.; Boyen, H.-G.; Ziemann, P.; Fauth, K. (Appl. Phys. Lett., 2007)

(untitled) - Penuelas, J.; Andreazza, P.; Andreazza-Vignolle, C.; Tolentino, H. C.; De Santis, M.; Mottet, C. (Phys. Rev. Lett., 2008)

(untitled) - Järvi, T. T.; Pohl, D.; Albe, K.; Rellinghaus, B.; Schultz, L.; Fassbender, J.; Kuronen, A.; Nordlund, K. (EPL, 2009)

(untitled) - Müller, M.; Albe, K. (Beilstein J. Nanotechnol., 2011)

(untitled) - Wang, R.; Dmitrieva, O.; Farle, M.; Dumpich, G.; Acet, M.; Mejia-Rosales, S.; Perez-Tijerina, E.; Yacaman, M. J.; Kisielowski, C. (J. Phys. Chem. C, 2009)

(untitled) - Han, L.; Wiedwald, U.; Kuerbanjiang, B.; Ziemann, P. (Nanotechnology, 2009)

(untitled) - Gruner, M. E. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B, 1996)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B, 1999)

Electronic Structure of Solids ’91 - Perdew, J. P. (Akademie Verlag, 1991)

(untitled) - Perdew, J. P.; Wang, Y. (Phys. Rev. B, 1992)

(untitled) - Vosko, S. H.; Wilk, L.; Nusair, M. (Can. J. Phys., 1980)

(untitled) - Gruner, M. E.; Adeagbo, W. A.; Zayak, A. T.; Hucht, A.; Entel, P. (Phys. Rev. B, 2010)

(untitled) - Pellarin, M.; Baguenard, B.; Vialle, J. L.; Lerme, J.; Broyer, M.; Miller, J.; Perez, A. (Chem. Phys. Lett., 1994)

(untitled) - Mackay, A. L. (Acta Crystallogr., 1962)

(untitled) - Ino, S. (J. Phys. Soc. Jpn., 1969)

(untitled) - Entel, P.; Gruner, M. E. (J. Phys.: Condens. Matter, 2009)

(untitled) - Dannenberg, A.; Gruner, M. E.; Hucht, A.; Entel, P. (Phys. Rev. B, 2009)

(untitled) - Gruner, M. E. (J. Phys.: Conf. Ser., 2010)

(untitled) - Clark, J. F.; Pinski, F. J.; Johnson, D. D.; Sterne, P. A.; Staunton, J. B.; Ginatempo, B. (Phys. Rev. Lett., 1995)

(untitled) - Dannenberg, A.; Gruner, M. E.; Entel, P. (J. Phys.: Conf. Ser., 2010)

(untitled) - Cheng, D.; Wang, W.; Huang, S. (J. Phys. Chem. B, 2006)

(untitled) - Calvo, F. (Faraday Discuss., 2008)

(untitled) - Cheng, D.; Cao, D. (Chem. Phys. Lett., 2008)

(untitled) - Müller, M.; Albe, K. (Phys. Rev. B, 2005)

(untitled) - Yang, B.; Asta, M.; Mryasov, O. N.; Klemmer, T. J.; Chantrell, R. W. (Acta Mater., 2006)

(untitled) - Müller, M.; Erhart, P.; Albe, K. (Phys. Rev. B, 2007)

(untitled) - Chepulskii, R. V.; Butler, W. H.; van de Walle, A.; Curtarolo, S. (Scr. Mater., 2010)

(untitled) - Zeng, H.; Sabirianov, R.; Mryasov, O.; Yan, M. L.; Cho, K.; Sellmyer, D. J. (Phys. Rev. B, 2002)

(untitled) - Brown, G.; Kraczek, B.; Janotti, A.; Schulthess, T. C.; Stocks, G. M.; Johnson, D. D. (Phys. Rev. B, 2003)

(untitled) - Gruner, M. E. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Lu, Z.; Chepulskii, R. V.; Butler, W. H. (Phys. Rev. B, 2010)

(untitled) - Mryasov, O. N.; Nowak, U.; Guslienko, K. Y.; Chantrell, R. W. (EPL, 2005)

(untitled) - Burkert, T.; Eriksson, O.; Simak, S. I.; Ruban, A. V.; Sanyal, B.; Nordström, L.; Wills, J. M. (Phys. Rev. B, 2005)

(untitled) - Lai, C.-H.; Ho, C.-H. (J. Appl. Phys., 2005)

(untitled) - Menshikov, A. Z.; Antropov, V. P.; Gasnikova, G. P.; Dorofeyev, Y. A.; Kazantzev, V. A. (J. Magn. Magn. Mater., 1987)

(untitled) - Meyer, G.; Thiele, J.-U. (Phys. Rev. B, 2006)

(untitled) - Menshikov, A. Z. (Physica B, 1988)

(untitled) - Ho, C.-H.; Lai, C.-H. (IEEE Trans. Magn., 2006)